Triple-drug antibiotic therapy for disseminated nocardial abscess in the mediastinum and brain of an immunocompetent patient: a case report - Yue Zhang; Zhongchun Qi; Hua Li; Hui Gao (BMC Infectious Diseases)
Abstract Background Nocardia are widely present in nature and considered opportunistic pathogens. They can result in hematogenous spread infection through the ruptured skin or respiratory tract when the host’s immune system is compromised. Currently, 119 species of Nocardia have been identified, with 54 capable of causing infections in humans. Nocardial brain abscesses are a rare intracranial lesion that accounts for only 2% of all brain abscesses, but have a mortality rate of 20–55%. This article reports a successfully cured case of mediastinal Nocardia infection with disseminated brain abscess. Case presentation The patient presented with intermittent chills, shivering, and fever, with the highest temperature of 39˚C, accompanied by shoulder and back pain, dizziness, and headaches. A chest-enhanced computed tomography (CT) revealed multiple enhanced nodulars in the bilateral hilum and mediastinum. A head-enhanced CT revealed scattered multiple ring-enhanced nodules in both cerebral hemispheres and the left cerebrum, accompanied by extensive surrounding edema. The mediastinal puncture tissue culture confirmed the growth of Nocardia. After twice discussions with multidisciplinary team (MDT) to rule out the possibility of mediastinal and intracranial metastatic tumors, we promptly initiated treatment with a triple-drug antibiotic regimen consisting of imipenem/cilastatin sodium, linezolid dextrose, and Trimethoprim-sulfamethoxazole (TMP-SMX). The patient ultimately achieved complete remission. Conclusions Mediastinal nocardiosis with disseminated brain abscesses is a rare condition that can be difficult to differentiate from brain metastases caused by lung cancer. Bacterial culture results, imaging features, and MDT discussions are crucial for accurate diagnosis and treatment. A triple-drug antibiotic regimen has been found to be effective in treatment with acceptable levels of toxicity.